An Optimized Energy Harvesting Circuit for Low-Power IoT Applications - Barua, Arnob; Rasel, Salauddin (MIST International Journal of Science and Technology, 2022)
The concept and development of an independent energy harvesting mechanism functioning intermittently are described in this paper. A power management circuit (PMC) that is self-regulating, an energy scavenging module, a circuit for charging batteries, as well as an electronic load are all a component of the system that has been proposed. This proposed circuit is designed to attain a fixed output power with a diverse input range. In the unavailability of an additional voltage supply, the PMC can react, maintain, and smartly control the electronic load's power supply. The self-powered energy accumulating technique is expected to be used in situations when supplied power is inadequate to drive the load properly, such as Internet of Things (IoT) applications. IoT is a dispersed architecture of reduced-power, limited-storage, lightweight, and nodes that are adaptive. The majority of embedded IoT devices and low-power IoT sensors are driven by short-life batteries that must be replaced every few years. This procedure is expensive and efficient energy regulation could be critical in enabling energy savings for connecting IoT devices. Experiments with the proposed PMC show that the voltage stored in the capacitor remained mostly fixed at 3.3V at widely diverse inputs that vary from 850mV to 4V. At 3.5V input voltage, a peak efficiency of 88.67% is achieved while the load resistance considered is 230Ω. MIJST, Vol. 10(1), June 2022: 41-48